Habitat use of common dolphin (Delphinus sp.) in the Mochima National Park, Sucre, Venezuela - Molero-Lizarraga, Alimar; Barreto, Guillermo; Cobarrubia-Russo, Sergio (J. Cetacean Res. Manage., 2022)
The common dolphin (Delphinus sp.) is one of the most common cetaceans in Venezuela. This study aims to describe habitat use in the Mochima National Park, a protected area under high anthropogenic pressure. Opportunistic surveys were conducted following a pre‐defined route from September 2009 to August 2010. Data such as the geographical position, group size, composition, behaviour were recorded at 5min intervals. A focal group‐follow methodology was used. A grid of 500×500m was constructed and each cell was characterised by environmental features and a Coefficient of Area Use (CAU) was calculated. A logistic regression model was applied to identify factors that explain use pattern. Seventy opportunistic surveys were conducted during which 86 groups of dolphins were observed. Dolphins occupied an area of 36km2, but Tigrillo inlet and to the northeast of the Caracas Islands were the areas most used. The common dolphins exhibited differential use, using shallow inshore waters most intensively and with probability of occurrence decreasing with increasing water depth and distance to the coast. They spent most of their time in feeding (40%) and socialising (24%) activities. Feeding and travelling behaviours were observed throughout the area studied, whereas socialising and resting activities were mainly concentrated in Tigrillo inlet, the Manare peninsula and the Caracas islands. Behaviour was mostly determined by season, depth, distance to the coast, group size and group composition. Throughout the year, the Park provided areas for refuge, feeding, and resting. It is therefore imperative to promote management and conservation policies that prevent any negative impacts from the increasing tourism and fishing activities we observed.